UTILIZAÇÃO DE RESÍDUOS DE CERÂMICA VERMELHA DA CONSTRUÇÃO CIVIL EM QUADRAS DE TÊNIS: ESTUDO DE CASO NO BRASIL - Schamne, Annelise; Nagalli, André; Nishiyama, Isabella; Badalotti, Isadora; Steffen, Luna (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This study presents an alternative to reuse red brick waste in the construction of tennis courts. To analyze the feasibility of this application a case study was realized in a brick industry located in Chapecó city, Santa Catarina, Brazil. The industry produces about 600.000 brick blocks per month and generates high amount of waste in the production process, transportation and reverse logistics of materials. To evaluate the applicability of these wastes in the construction of tennis courts some criteria related to cost, infrastructure, market, financial return, production process and partnership were considered. Investigations concluded that if the brick industry invests in building of one or two tennis courts with twoyear maintenance, it takes only three years to recover all the initial investment. Therefore, reuse red brick waste in construction of tennis courts is an alternative to minimize waste generated in brick industries.